Analysis of Mentor Competency Standard Setting in Talent Management Policy in Indonesian National Police (POLRI) - Temmy Esterlita; Mala Sondang Silitonga (Green Publisher Indonesia, 2026)
This study analyzes the factors determining the mentor competency standards within the Talent Management Policy of the Indonesian National Police (Polri). The research aims to formulate an effective mentoring framework that supports human resource excellence in line with Indonesia’s 2045 vision. Using a qualitative approach, the study explores the dynamics between mentors, talents, and policy implementers through in-depth interviews and document analysis. The research integrates the Leader–Member Exchange (LMX) theory, Person–Environment Fit model, and Competency Model by Boyatzis and Spencer & Spencer to identify key dimensions influencing mentor effectiveness—trust, respect, and mutual obligation. Findings indicate that mentor competence is shaped by integrity, professional expertise, emotional intelligence, and commitment to organizational values. However, implementation challenges persist due to limited competency-based training, high workload, and the lack of standardized evaluation mechanisms. Through the SOAR (Strengths, Opportunities, Aspirations, Results) analysis, four strategic directions are proposed: institutionalizing core mentoring values, leveraging digital transformation, establishing national competency standards, and promoting cross-agency collaboration. The study concludes that strengthening mentor competencies is not merely an administrative reform but a transformational effort to cultivate adaptive, ethical, and service-oriented leadership within Polri. These findings are expected to contribute to the development of a professional, sustainable talent management system supporting Indonesia’s human resource transformation toward Indonesia Emas 2045.